Use of whole-genome sequencing to investigate a cluster of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infections in emergency department personnel. (4th October 2022) - Chan, Ernest R.; Jones, Lucas D.; Redmond, Sarah N.; Navas, Maria E.; Kachaluba, Nataliya M.; Zabarsky, Trina F.; Bhullar, Davinder; Cadnum, Jennifer L.; Zimmerman, Peter A.; Donskey, Curtis J.
Abstract: Several recent reports have raised concern that infected coworkers may be an important source of severe acute respiratory coronavirus virus 2 (SARS-CoV-2) acquisition by healthcare personnel. In a suspected outbreak among emergency department personnel, sequencing of SARS-CoV-2 confirmed transmission among coworkers. The suspected 6-person outbreak included 2 distinct transmission clusters and 1 unrelated infection.